2021
DOI: 10.1002/nafm.10622
|View full text |Cite
|
Sign up to set email alerts
|

Long‐Term Trends in Juvenile Atlantic Sturgeon Abundance May Signal Recovery in the Hudson River, New York, USA

Abstract: Overfishing, bycatch, and habitat loss and alteration during the late 19th century to the end of the 20th century caused significant declines in Atlantic Sturgeon Acipenser oxyrinchus stock abundances along the Atlantic coast. To prevent further stock reductions, a coastwide harvest moratorium was implemented in 1998. With fishery‐dependent data unavailable to inform stock management, fishery‐independent surveys contribute vital information for monitoring population trends by providing data for evaluating the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 40 publications
(102 reference statements)
2
7
0
Order By: Relevance
“…We found that catch rates were highest ~27 km downstream of the salt front in mesohaline waters, declined abruptly in higher salinity waters, and declined gradually into fresh water, with the highest catch rate location in some years closer to the predicted salt front, which supports previous research showing positive relationships between catch rates and salinity (Pendleton & Adams, 2021) and distributional observations across multiple systems (Fox & Peterson, 2019; Haley et al, 1996; Hatin et al, 2007; Moser & Ross, 1995; Secor et al, 2000). Availability is described as the ratio between the population range and the fraction affected by the survey (Arreguin‐Sanchez, 1996).…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…We found that catch rates were highest ~27 km downstream of the salt front in mesohaline waters, declined abruptly in higher salinity waters, and declined gradually into fresh water, with the highest catch rate location in some years closer to the predicted salt front, which supports previous research showing positive relationships between catch rates and salinity (Pendleton & Adams, 2021) and distributional observations across multiple systems (Fox & Peterson, 2019; Haley et al, 1996; Hatin et al, 2007; Moser & Ross, 1995; Secor et al, 2000). Availability is described as the ratio between the population range and the fraction affected by the survey (Arreguin‐Sanchez, 1996).…”
Section: Discussionsupporting
confidence: 90%
“…Most conditions of this protocol were completed annually during 2004–2015, although occasional samples were collected at temperatures below 4°C. We subset catch data to include only fish with total length ≤ 950 mm, which corresponds to the estimated upper length of an age‐5 Atlantic Sturgeon (Dunton et al, 2016; Pendleton & Adams, 2021). Restricting size of fish included in the index limited the potential effect of larger non‐natal sub‐adult fish migrating between estuaries.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations